PELATIHAN PEMBUATAN MODUL AJAR KREATIF SEBAGAI UPAYA MENINGKATKAN EFEKTIVITAS PROSES PEMBELAJARAN DI SD NEGERI 1 WANASARI TABANAN - Wayan, Juliawan; Ni Wayan Suastini; Ni Komang Sri Yuliastini; I Wayan Susanta; Nyoman Rajeg Mulyawan; Roro Dwi Umi Badriah; Sri Datuti (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
This community service aims to enhance the effectiveness of the teaching and learning process at SD Negeri 1 Wanasari by empowering teachers to design engaging, contextual, and student-centered teaching materials. The activity is driven by the need for learning media that can foster active student participation and improve comprehensive understanding of the subject matter. The training methods include material presentations, interactive discussions, and hands-on practice in developing teaching modules based on the Merdeka Curriculum. The results of the activity indicate an improvement in teachers' understanding of creative teaching module concepts and their ability to develop innovative and applicable modules. Through this training, it is expected that teachers will be able to create a more enjoyable and meaningful learning environment, thereby positively impacting student learning outcomes.